Primate HPT Axis Response to the Peripheral Kisspeptin Challenge Under Different Time Periods of Food Restriction in Monkeys - Wahab, F.; Atika, B.; Huma, T.; Shahab, M. (Hormone and Metabolic Research, 2014)
Metabolism and reproduction are closely linked. Both long- and short-term fasting-induced metabolic deficiency suppresses reproductive function in mammals. Recently, we have shown that 48-h fasting-induced metabolic deficiency attenuates the reproductive axis responsiveness to peripheral kisspeptin injection in the sexually mature monkeys. But currently there is no data to show whether shorter time periods of fasting also alter the reproductive axis responsiveness to kisspeptin. Therefore, this study was aimed to examine the reproductive axis responsiveness to kisspeptin administration in the adult male rhesus monkey fasted for 12-, 18-, and 24h. Intravenous boli of vehicle (1ml) and human kisspeptin-10 (KP10; 50μg) were given to 5 intact sexually mature male rhesus monkeys in both fasting (12-, 18-, 24-h) and ad libitum feeding conditions. Specific immunoassays were used to determine plasma hormones concentrations. KP10 injection highly stimulated testosterone secretion in all conditions. However, mean testosterone concentrations in 3-h post-KP10 injection period were significantly (p<0.01) decreased in 18- and 24-h fasted monkeys when compared to 12-h fasted and fed monkeys. Moreover, 18- and 24-h fasting conditions also significantly (p<0.05) delayed the duration to the first significant increase in T levels after KP10 injection. Vehicle injection did not alter these parameters in any conditions. Present results indicate that 18- and 24-h fasting conditions suppressed the testosterone response to KP10 administration both in initiation and quantity. These results suggest that 18- and 24-h fasting-induced inhibition of the reproductive functions in the mature male macaque may partly involve attenuation in the reproductive axis responsiveness to endogenous kisspeptin stimulation.
Keywords: fasting; HPT axis; GnRH; Kiss1; Kiss1r; testosterone; monkey